Reduced graphene oxide/Bi4O5Br2 nanocomposite with synergetic effects on improving adsorption and photocatalytic activity for the degradation of antibiotics. (February 2021) - Xu, Mengwen; Wang, Yanying; Ha, Enna; Zhang, Huijuan; Li, Chunya
Abstract: A photocatalyst based on the integration of reduced graphene oxide (rGO) with Bi4 O5 Br2 nanosheets was facilely prepared and was confirmed by transmission electron microscope, scanning electron microscope, X-ray diffraction and Raman spectroscopy. The integration of rGO can effectively improve the adsorption and the photocatalytic properties of Bi4 O5 Br2 nanosheets towards the target antibiotics under visible light irradiation. rGO/Bi4 O5 Br2 nanocomposite containing 1.0 wt% of rGO exhibits the optimal adsorption and photocatalytic activity towards ciprofloxacin (CIP), norfloxacin (NOR) and tetracycline (TC). The removal efficiencies of CIP, NOR and TC are 97.6%, 80.7% and 98.7%, which are higher than that obtained with Bi4 O5 Br2 nanosheets. The capture experiments and ESR data show that ·O2 −, OH· and h + are the main active species that participated in the photodegradation system. This work provides a simple strategy to integrate rGO with Bi x O y X z (X = Cl, Br, I) nanosheets to construct effective photocatalysts for the degradation of antibiotics. Graphical abstract: Image 1 Highlights: Reduced graphene oxide (rGO) integrated with Bi4 O5 Br2 nanosheets was facilely prepared. rGO/Bi4 O5 Br2 nanocomposites were employed as photocatalyst for degradation of antibiotics. Photodegradation activity and mechanism of rGO/Bi4 O5 Br2 towards antibiotics was demonstrated.